Housewives’ Waste Reduction Practices: A Study of Sustainable Lifestyles in Batam City - Nabillah Azwa; Lubna Salsabila; Iranda Firiansyah; Sahat Sianturi (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to examine the role of housewives in waste reduction through the implementation of 3R (Reduce, Reuse, Recycle) principles, serving as a means to influence waste management behaviors and foster the adoption of a community-driven circular economy. This approach is designed to involve the broader business environment and city government. The research employs a descriptive qualitative method, focusing on the collection of data and information without reliance on quantitative calculations.The findings highlight that the participation of housewives plays a significant role in engaging individuals and groups in waste management activities. The study underscores the importance of community involvement in providing suggestions, expressing opinions, and actively participating in waste management initiatives. The research emphasizes that housewives play a critical role in waste collection, aligning with the principles of 3R. This role contributes to fostering clean and healthy living behaviors within communities, reinforcing the essential contribution of housewives in achieving sustainable waste management practices.